PERAN DUNIA PENDIDIKAN DAERAH KABUPATEN KARIMUN DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA GUNA MENCIPTAKAN DAYA SAING INVESTASI DAN LAPANGAN KERJA DALAM RANGKA PEMBANGUNAN NASIONAL (DAERAH PERBATASAN) - Nurdin Basirun (Universitas Negeri Jakarta, 2012)
Local government Kabupaten Karimun contend thats improvement of human resource quality (SDM) is priority of area development to competitive ability, investment and employment in order to national development. Resources Development that with quality must cover development competitive SDM, with character, development as the citizen Indonesia that can esteem religion and cultural â€œkebhinekaanâ€, human being, fatherland love, democratic and fair. To develop SDM are referred as, become duty of educator energy to be able to their patterned thinking fox. Expected educator is educator that have energy mental combatant that can form student that independence, think, personality (be, trusted, honesty), work ethics, clever and skillful according to concept of archipelagic country development for example grow maritime knowledge for society and government in order to development Indonesia oceanic orientation; and improved human resource capacities that with vision of oceanic pass by development of oceanic science and technology.